Effects of Luffa Cylindirica Fibers on Some Mechanical and Printability Properties of Handsheets - (:unkn) unknown (ASIAN JOURNAL OF CHEMISTRY, 2011)
Luffa cylindrical fibers were both treated with distilled water and acetic acid under an ultrasonic energy media, beaten at a laboratory refiner (PFI) and-blended with old corrugated pulps to produce a number of packaging grade paper products. Acetic acid treatment in the ultrasonic energy atmosphere resulted in a higher amount of weight lost (7.2%) giving thinner and flexible fibers compared to that of treated by distilled water. Mechanical and printing properties of handsheets were negatively affected by the presence of luffa fibers. The surface roughness and the air permeability of resultant papers were also greatly increased by luffa fiber addition. It is concluded that luffa fibers make handsheets quite porous and permeable which directly reduced handsheet strength and printing qualities. Luffa fibers can be perfectly used in the production of permeable packaging materials with the addition of some strength additives.
Keywords: Non-woods; Biomaterials; Luffa; Modification; Sonication; Printability; ULTRASONIC ENERGY; CYLINDRICA FIBERS; DROPLET; WATER; REINFORCEMENT; PRETREATMENT; PENETRATION; NETWORKS; BEHAVIOR; TENSILE